Understanding artificial intelligence - Sabouret, Nicolas (Boca Raton : Chapman & Hall/CRC, 2021)
Artificial Intelligence (AI) fascinates, challenges and disturbs us. There are many voices in society that predict drastic changes that may come as a consequence of AI - a possible apocalypse or Eden on earth. However, only a few people truly understand whatAI is, what it can do and what its limitations are. Understanding Artificial Intelligence explains, through a straightforward narrative and amusing illustrations, how AI works. It is written for a non-specialist reader, adult or adolescent, who is interested in AI but is missing the key to understanding how it works. The author demystifies the creation of the so-called "intelligent" machine and explains the different methods that are used in AI. It presents new possibilities offered by algorithms and the difficulties that researchers, engineers and users face when building and using such algorithms. Each chapter allows the reader to discover a new aspect of AI and to become fully aware of the possibilities offered by this rich field.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence; COMPUTERS / Artificial Intelligence; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Machine Theory